Audio engineering 101 a beginner's guide to music production - Dittmar, Tim (Routledge, 2018)
"Pratical, concise, and approachable, Audio Engineering 101, Second Edition covers everything aspiring audio engineers need to know to make it in the recording industry, from the characteristics of sound to microphones, analog versus digital recording, EQ/compression, mixing, mastering, and career skills. Filled with hand-on, step-by-step technique breakdowns and all-new interviews with active professionals, this updated edition includes instruction in using digital consoles, iPads for mixing, audio apps, plug-ins, home studios, and audio for podcasts. An extensive companion website features fifteen new video tutorials, audio clips, equipment lists, quizzes, and student exercises"--Publisher's website